"It`s absolutely essential": sport and performance psychology practitioners` perspectives on training, use, and importance of debriefing in applied work - Maurice, S.; Byrd, M.; Crawford, H.; Johnson, K.; He, J.; Charalambous, C. (The Sport Psychologist, 2023)
Debriefing is commonly used in sport and performance psychology (SPP), but little has been done to expand debriefing education and training experiences. The researchers sought to examine SPP practitioners` education and training on debriefing and how it is used in their applied work. This study had two phases (Phase I, n = 143; Phase II, n = 13). During Phase I, researchers developed a 16-item questionnaire regarding demographics and debriefing training, use, and importance. Many participants debriefed every session (46%) and rated debriefing as extremely (53.1%) or very important (39.2%). Participants were unsatisfied with their training (55%) and desired more debriefing training from coursework (65%). Three themes were identified in Phase II interviews: training and education, use of debriefing, and importance of debriefing. With limited research in SPP about debriefing, this study furthers knowledge about how debriefing is used in practice and how training experiences can be improved.